Youth In-Scene at School: education in the encounter with the city - Lorenna Pinheiro Rocha; Maria Celina Peixoto Lima (Universidade Federal do Rio Grande do Sul, 2021)
The traditional alliance between education and laborhas been taking shape in the apparent adherence of educational practices to the machinations of capitalism. Starting from the analysis of the effects of the entry of this discursive configuration into schools, our hypothesis is that we are watching the transition from a cultural qualification, as discussed by Adorno, to a professional qualification. In this article, we intend to present the results of a research through intervention we accomplished in the context of a photography workshop, and which point to the potential of art to subvert the logic of a technical education, creating another scenario for the encounter between education and the city, beyond one that is guided by inserting the young into the labor market.